Kepuasan kerja pemoderasi kompensasi terhadap kinerja pegawai - Rahim, Muhammad Zaki Fauzi Rahman; Nursyamsi, Idayanti; Hakim, Wardhani (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to analyze the effect of compensation on employee performance with job satisfaction as an intervening variable. This study uses a quantitative approach, the population of this study were employees of PT. Lintas Antar Nusa Makassar amounted 100 people. Sampling was carried out using a saturated sample technique which all the population was sampled. The research was conducted at PT. Lintas Antar Nusa Makassar, which is a company engaged in the export of fishery products. Data was collected using by survey method on 100 respondents. The results showed that compensation with indicators of salary, benefits, social benefits and career rewards had a significant effect on job satisfaction, employee job satisfaction includes indicators of working conditions, job security, communication, supervision, and co-workers have a significant and positive effect on employee performance. In the other side, compensation has a significant effect on employee performance if moderated by job satisfaction.